Caracterização das propriedades termoacústicas do hidrogel de carbopol visando a confecção de phantoms para HIFU mimetizando tecidos biológicos - Santos, Nathalia Cristina de Alcantara Nogueira dos (2019)
This work presents the development of Carbopol-based hydrogels, containing cellulose and castor oil for use as biological tissue mimic materials. The acoustic properties were characterized between 1 MHz and 7.5 MHz and thermal properties between 25 ºC and 85 ºC. The incorporation of cellulose and emulsion in the hydrogel, caused a change in the attenuation a pure gel from a coefficient of 0.06 dB cm-1 (1 MHz) to 0.11 and 0.30 dB cm-1 (1 MHz) for the gels with 3% cellulose addition and nanoemulsified gel, respectively. Regarding the ultrasonic propagation speed, it was concluded that a pure gel and the gel from 3% cellulose addition the value remained around 1511 m s-1 , while the nanoemulsified gel presented slightly faster propagation speed, changing to 1525 m s-1 . The specific heat value obtained for hydrogels was 3.6 to 3.9 J g -1 K -1 . For thermal conductivity, the value was approximately 0.6 W m-1 K -1 and for thermal diffusivity, the values found in this study were from 0.143 to 0.148 mm-2 s -1 . The proposed hydrogels, show that Carbopol polymer is a promising material for the manufacture of ultrasonic phantoms and is useful for analyzing the behavior of high intensity focused ultrasound irradiation specimens.